Analyzing Sediments Assessment and Distribution Using Bathymetric Survey: A Comprehensive Study of the Abu Abdullah Canal, Southern Iraq - Khaleefa, Usama Qasim; Hussein, Meelad A.; Shareef, Najed Faisal; Almayahi, Dawod S.; Chasib, Sajjad K. (Marine Science Department Diponegoro University, 2024)
The Abu Abdullah canal, an essential part of the Garma River, serves as the feeder to the water injection station for the Basrah Oil Company's southern region's oil fields, playing a significant strategic. This study thoroughly investigates the sedimentation rate and distribution processes within this critical canal. The canal was built in the 1980s, with a depth of 3 meters planned. In 2017, RSK Company, in partnership with the Basrah Oil Company, started a comprehensive bathymetric survey of the canal to investigate its depth characteristics. The survey yielded intriguing results, revealing notable variations in depth along the canal's course. Depths ranged from 0.4 m at the canal's edges to an average of 1.6 m in the middle, indicating a significant decrease of 1.4 m in the middle region and 2.6 m at the edges. The collapse of the canal banks, induced by the proximity of Buffalo breeders' residences near the canal, is the primary source of this depth variation. Incidental entry and traversal of Buffaloes lead to gradual structural degradation of the banks, exerting a substantial influence on sediment distribution within the canal. Moreover, Buffalo standing in the middle of the canal induces compression on the channel bottom, altering the sediment transport dynamics. The study's outcomes are critical for sustainable canal management and environmental conservation. Understanding the complicated interaction between human activities and natural processes for shaping canal morphology is vital for developing effective strategies aimed at safeguarding canal banks and preserving their ecological functions. This research significantly advances the understanding of canal sediment dynamics, presenting practical applications in hydraulic engineering and environmental management.